The practice of modern family planning methods amongst married Muslim women in Katsina, Katsina State, Nigeria / Amina Lawal Mashi and Rohana Yusof - Lawal Mashi, Amina; Yusof, Rohana (Division of Research and Industry Linkages, UiTM Melaka, 2014)
The study is aimed at identifying the changing attitude of married Muslim women on the acceptance and usage of modem family planning methods within the Katsina metropolis. Two hundred women were selected randomly from the four maternal health centres in Katsina metropolis for the study. They were socio-demographically characterised by different ages, varied educational status but from the same ethnic and religious background. Questionnaires were used to gather the data from the four maternal centres; which were administered through the nurses in charge of the four family planning units in the four Maternal Health centres. The results showed that the respondents (i.e. Married Muslim women) in spite of their cultural and religious background have good knowledge of modem family planning methods and have high acceptance of modem family planning contraceptives. The results also indicated that age or religious beliefs do not constitutes hindrance to the acceptance and practice of modem family planning contraceptives. However, the results indicated that acceptance of modem family planning contraceptives is low amongst the rural women who are illiterates. The study recommends a holistic approach (i.e. all stakeholders, parents, husbands, religious/ educational institutions, NGOs and government) towards the acceptance and practice of family planning in order to achieve the goals of 2004 national policy on population. This can be achieved through more enlighten campaigns particularly to attract less educated rural women on the use of modem contraceptives to space their children, establishment of more health maternal centres in the rural areas, provision of free counselling services and contraceptives as a motivation towards acceptance and practice of family planning methods.